PENGARUH WAKTU TUNGGU TERHADAP KEPUASAN PASIEN DI PUSKESMAS MAUK KABUPATEN TANGERANG BANTEN - Octaviani Dewi, Mella; Marsepa, Eva (Nusantara Hasana Journal, 2021)
Waiting time is one of the most important aspects that can affect the level of patient satisfaction in the services received, especially in health facilities. The higher the service provided will be an advantage for the health center. The research design used by the researcher is an analytic survey using a cross sectional design, accidental sampling technique with a total of 100 respondents who seek treatment at the Mauk Public Health Center, Tangerang Regency. The statistical test used is the Wilcoxon test. Wilcoxon test, obtained p-value 0.000 > 0.05, which means that there is an effect of waiting time on patient satisfaction at the Mauk Public Health Center, Tangerang Regency. With very low influence strength values ​​on both variables.